2021
DOI: 10.1021/acsabm.0c01545
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and Nanotechnology-Based Sensing Methods for SARS Coronavirus (2019-nCoV)

Abstract: Ongoing pandemic coronavirus (COVID-19) has affected over 218 countries and infected 88,512,243 and 1,906,853 deaths reported by Jan. 8, 2021. At present, vaccines are being developed in Europe, Russia, USA, and China, although some of these are in phase III of trials, which are waiting to be available for the general public. The only option available now is by vigorous testing, isolation of the infected cases, and maintaining physical and social distances. Numerous methods are now available or being developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 105 publications
0
29
0
Order By: Relevance
“…IgG is considered as an indicator of the present or prior infection, while IgM is an indicator of the initial stage of infection, which can persist in the body for more than three months [67] , [82] . Recent efforts have demonstrated that IgG and IgM antiviral antibodies can be identified in the human serum samples infected with SARS-CoV-2 [90] , [91] , [92] , [93] .…”
Section: Detection Of Immunoglobulin For Sars-cov-2 Virusesmentioning
confidence: 99%
“…IgG is considered as an indicator of the present or prior infection, while IgM is an indicator of the initial stage of infection, which can persist in the body for more than three months [67] , [82] . Recent efforts have demonstrated that IgG and IgM antiviral antibodies can be identified in the human serum samples infected with SARS-CoV-2 [90] , [91] , [92] , [93] .…”
Section: Detection Of Immunoglobulin For Sars-cov-2 Virusesmentioning
confidence: 99%
“…A field-effect transistor (FET) based biosensing device has several advantages, including the ability to make very sensitive and instantaneous measurements using small amounts of analytes for detecting COVID-19 in clinical samples. The sensor uses graphene sheets coated with a specific antibody immobilized against SARS-CoV-2 spike protein [148][149][150][151]. Graphene is selected because of its high electron mobility, electrical and thermal conductivity, and mechanical strength.…”
Section: Graphene Field Effect Transistormentioning
confidence: 99%
“…Affinity sensors for diagnosis has been discussed by Drobysh et al [ 76 ]. Shetti et al described conventional and nanotechnology-based sensors for COVID-19 [ 77 ]. Recent efforts in the applications of colloidal particles and nanoparticles for the diagnostics and treatment of COVID-19 have also been summarized [ 78 , 79 ].…”
Section: Perspectives and Conclusionmentioning
confidence: 99%